Biochemical and genetic predictors and correlates of response to lamotrigine and folic acid in bipolar depression: Analysis of the CEQUEL clinical trial - Tunbridge, E; Attenburrow, M; Gardiner, A; Rendell, J; Hinds, C; Goodwin, G; Harrison, P; Geddes, J (John Wiley and Sons, Ltd., 2017)
Objectives CEQUEL (Comparative Evaluation of QUEtiapine plus Lamotrigine combination versus quetiapine monotherapy [and folic acid versus placebo] in bipolar depression) was a double‐blind, randomized, placebo‐controlled, parallel group, 2×2 factorial trial that examined the effect of adding lamotrigine and/or folic acid (FA) to quetiapine in bipolar depression. Lamotrigine improved depression, but its effectiveness was reduced by FA. We investigated the baseline predictors and correlates of clinical response, and the possible basis of the interaction. Methods The main outcome was change in depressive symptoms at 12 weeks, measured using the Quick Inventory for Depressive Symptoms—self report version 16 (QIDS‐SR16). We examined the relationship between symptoms and lamotrigine levels, and biochemical measures of one‐carbon metabolism and functional polymorphisms in catechol‐O‐methyltransferase (COMT), methylene tetrahydrofolate reductase (MTHFR) and folate hydrolase 1 (FOLH1). Results Lamotrigine levels were unaffected by FA and did not differ between those participants who achieved remission and those with persisting symptoms. When participants with subtherapeutic serum levels were excluded, there was a main effect of lamotrigine on the main outcome, although this remained limited to those randomized to FA placebo. None of the biochemical measures correlated with clinical outcome. The negative impact of FA on lamotrigine response was limited to COMT Met carriers. FOLH1 and MTHFR had no effect. Conclusions Our results clarify that FA's inhibition of lamotrigine's efficacy is not a pharmacokinetic effect, and that low serum lamotrigine levels contributed to lamotrigine's lack of a main effect at 12 weeks. We were unable to explain the lamotrigine−FA interaction, but our finding that it is modulated by the COMT genotype provides a starting point for follow‐on neurobiological investigations. More broadly, our results highlight the value of including biochemical and genetic indices in randomized clinical trials.